RANCANG BANGUN ALAT DETEKSI KADAR GULA DARAH NON-INVASIF BERBASIS BIOSENSOR OPTIK METODE NEAR-INFRARED PHOTOPLETHYSMOGRAPHY (NIR PPG) TERINTEGRASI APLIKASI - Hidayatulloh, Fajrul Fallaah; Nurussa’adah, n/a; Zainuri, Akhmad (Jurnal Mahasiswa TEUB, 2025)
Invasive methods used in glucometers, which require blood samples through needle pricks, often cause discomfort, making many patients reluctant to monitor their blood glucose regularly. This study developed non-invasive blood glucose monitoring technology using the MAX30102 sensor, which employs the photoplethysmography method with a near-infrared wavelength of 880 nm. Blood glucose levels were estimated based on the range in maximum and minimum infrared intensity values (RMM Amplitude), processed using a linear regression equation derived from a dataset of 20 respondents. Testing was conducted by comparing the prototype results with the EasyTouch glucometer, standardized by the Indonesian Ministry of Health. The results showed a positive correlation between RMM Amplitude and glucometer readings, with the device achieving an accuracy of 88,7% for blood glucose levels below 120 mg/dL. The supporting application successfully displayed data in graphical form, provided notifications, and offered recommendations when blood glucose levels were outside the normal range. Keywords: Diabetes Mellitus, Blood Glucose, Non-invasive, Near-Infrared, Photoplethysmography.